PERLINDUNGAN DATA PRIBADI KONSUMEN PADA PENYELENGGARAAN SISTEM ELEKTRONIK : Studi Komparatif Antara Indonesia dan Uni Eropa - Rizkia Aulia Jarief (2023)
Based on data reportal on January 2022, sum of internet users in Indonesia has 204,7 m peoples and level of internet penetration has 73,7% from all population at early year 2022. That being full attention for control about protect the personal data on electronic system. Before theres constitusion about personal data, Indonesia regulation still general. To make a right regulation than Indonesia have to do a comparative study with another country who have good regulation and one of that is Uni Eropa. The main function of comparative law is to being place for find the different from two or more law system on legal issues. Therefore, uses juridical normative method of the research will explain the aim it for compare the law between Indonesia and Uni Eropa about protect consumen personal data on electronic system and to know the exact regulation about that.